Implementation of E-Performance of State Civil Apparatus in the General Bureau of the Regional Secretary of North Sulawesi Province - Florence Filly Umpel,; Abdul Rahman Dilapanga,; Fitri Mamonto, (Technium Social Sciences Journal, 2025)
In the digital era, performance management of the State Civil Apparatus (ASN) is a challenge that requires innovation to improve efficiency and accountability. This research aims to analyze the effectiveness of the implementation of the e-Performance system at the General Bureau of the Regional Secretariat of North Sulawesi Province, and identify technical and non-technical obstacles faced. The research used a descriptive qualitative approach with data collection through interviews, observation, and documentation. The results showed that e-performance helps improve efficiency, transparency, and accountability of ASN performance through a web-based system that facilitates recording and evaluating tasks. However, its implementation faces obstacles such as limited technological infrastructure, lack of training, and employee resistance to new technology. Technical constraints, such as network access disruptions, as well as non-technical constraints, such as low employee understanding of the benefits of the system, affect the effectiveness of implementation. In conclusion, e-performance is a strategic innovation in ASN performance management. However, its success requires management support, infrastructure improvement, continuous training, and changes in work culture. By overcoming these obstacles, e-performance can become a foundation in building a more modern and accountable bureaucracy.